The Debate Over Slavery : Antislavery and Proslavery Liberalism in Antebellum America. - Ericson, David F. (NYU Press, 2000)
Frederick Douglass and George Fitzhugh disagreed on virtually every major issue of the day. On slavery, women's rights, and the preservation of the Union their opinions were diametrically opposed. Where Douglass thundered against the evils of slavery, Fitzhugh counted its many alleged blessings in ways that would make modern readers cringe. What then could the leading abolitionist of the day and the most prominent southern proslavery intellectual possibly have in common? According to David F. Ericson, the answer is as surprising as it is simple; liberalism. In The Debate Over Slavery David F.